Effect of Drip Irrigation on Physico-chemical Characteristics of Pomegranate Fruits in Arid Region - Prasad, R N; Mali, P C (Annals of Arid Zone, 2016)
The effect of drip irrigation on physico-chemical characteristics of pomegranate fruits revealed that physical parameters of the fruit such as weight of fruit (g), juice content, both on fruit as well as aril weight basis, and seed content on fruit . ’weight basis, were significantly higher. in drip-irri:1at d Iants.as, compared to con rol plants. Application of water through dnp @ 8 L h sIgnificantly reduced the crackmg of fruits (20.9%) in comparison to control (50.8%). The chemical parameters such as TSS, total sugars, reducing sugars and pH of the juice decreased with increasing wate under drip irrigation, whereas the acidity and non-reducing sugars increased ..